Unsteady Loading on a Tidal Turbine Due to the Turbulent Wake of an Upstream Turbine Interacting with a Seabed Ridge - Sulaiman Hurubi; Hannah Mullings; Pablo Ouro; Peter Stansby; Tim Stallard (Energies)
Tidal sites can present uneven seabed bathymetry features that induce favourable or adverse pressure gradients and are sources of turbulence, and so are likely to affect the operation, performance, and wake recovery dynamics of deployed tidal-stream turbines. Large-eddy simulations are conducted to analyse the unsteady loading of a tidal turbine subjected to the wake of an upstream turbine that interacts with a two-dimensional ridge located between the two turbines. Relative to an isolated turbine, blade fatigue loading is increased by up to 43% when subject to the wake of a turbine located 8 turbine diameters upstream interacting with a ridge located 2 turbine diameters upstream, whereas for the same spacing, the turbine wake led to a limited 6% reduction in loading and the ridge wake only caused a 79% increase. For larger spacings, the trends were similar, but the magnitude of difference reduced. Predictions of fatigue loads with a blade element momentum model (BEMT) provided a good agreement for flat bed conditions. However, the ridge-induced pressure gradient drives rapid spatial change of coherent flow structures, which limits the applicability of Taylor’s frozen turbulence hypothesis adopted in the BEMT. Reasonable prediction of rotor loading with BEMT was found to be obtained using the turbulent onset flow field at a plane one-diameter upstream of the turbine. This is more accurate than use of the planes at the rotor plane or two-diameters upstream, as coherent structures represent those modified by wake recovery and rotor induction in the approach flow to the turbine.